CFIUS and China in the post-COVID environment - Mario Mancuso (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
In this Perspective, former CFIUS decision-maker Mario Mancuso sets forth a framework for understanding the policy and practice of CFIUS in the post-COVID world. Specifically, this Perspective assesses how COVID has accelerated and intensified a profound suspicion of China in the US, with far-reaching policy, political, economic, and commercial impacts.
Keywords: 330